ANALISIS RASIO PIUTANG UNTUK MENILAI PIUTANG TAK TERTAGIH DAN AKTIVITAS PENAGIHAN PIUTANG PADA PT BSM - Khiftia Rachmah Hidayah; Anik Yuliati (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Every company or business in increasing revenue, profits, and company operational activities such as increasing production volume requires a strategy, one of which is by providing sales of goods or services on credit. The sale of these goods or services will give rise to receivables. In addition to being able to increase profits and increase the company's production volume, receivables will also cause losses, disrupt operational activities, and have an impact on PT BSM's financial health if the receivables cannot be collected, so the purpose of this study is to find out how much uncollectible receivables are and assess the receivables collection activities carried out at PT BSM during the 2021-2023 period. To analyze the ratios related to receivables, it can be calculated by calculating the turnover of receivables, the average day of collection of receivables, the arrears ratio, and the collection ratio. However, in accordance with the topic discussed by the researcher, namely by using the ratio analysis related to receivables recorded by the author in this study, namely using the analysis of the arrears ratio and the collection ratio, which was obtained as a result of each PT BSM's ratio during the 2021-2023 period, which was 1.38% for the arrears ratio and 98.6% for the collection ratio. It can be concluded that the small risk of uncollectible receivables due to the total percentage of arrears ratio ≤ 3% and the high collection activity of receivables due to the total percentage of collection ratio > 97% at PT BSM during the 2021-2023 period.